PENGEMBANGAN E-MODUL BERORIENTASI HIGHER ORDER THINKING SKILLS (HOTS) PADA PELAJARAN ILMU PENGETAHUAN ALAM (IPA) KELAS VI SEKOLAH DASAR - Aldi Qoridatullah; Sholeh Hidayat; Ajat Sudrajat (LPPM Universitas Muhammadiyah Muara Bungo, 2021)
Learning resources that do not facilitate students to improve higher-order thinking skills result in the achievement of learning objectives. This is because higher order thinking skills (HOTS) are one of the skills that students must have in current learning. This study aims (1) To describe and analyze the level of ability of students in solving HOTS questions using HOTS oriented e-modules in science for 6th grade, (2) To describe the form or results of a products HOTS oriented modules in sciences for 6th grade, (3) To describe and analyze the feasibility level of using HOTS oriented e-modules in science for 6th grade, (4) To describe and analyze the effectiveness level of using HOTS oriented e-modules in science lessons in grade 6th in improving student learning outcomes. The research type used in this research is research and development (Research and Development) Borg and Gall. The subjects of this study were students of grade VI SD Negeri Kayu Agung for the 2020/2021 academic year. To find out the response of teachers and students to the developed e-module was obtained using a questionnaire method.The results obtained show that (1) The use of e-modules oriented to HOTS in science for 6th grade can improve students abilities in solving HOTS type questions, which is marked by an increase in student learning outcomes scores in the pre test and post test. (2) The form or result of the HOTS oriented e-module product in science lessons for grade 6th is in the form of a link, so that it is easily accessed by students using a device connected to an internet connection. (3) HOTS oriented e-module in science for 6th grade is feasible to be used as teaching material based on the results of the material expert validation test obtaining an average score of 88.33 in the very good category, the results of the media expert validation test obtained a score of 88.00 with a very good category, and the results of the validation test for learning experts obtained an average score of 82.92 in the very good category. (4) HOTS orientation in science for 6th grade is effective for improving student learning outcomes, which is indicated by an increase in the pre-test average score of 65.00 to an average post-test score amounting to 76.33. Meanwhile, the follow-up to this research is to develop other e-modules for learning general subjects in elementary schools.